Comparative study of microwave and conventional sintering on properties of zirconia / Nurhusna Zulkifli - Nurhusna, Zulkifli (2018)
In the past three decades, zirconia based ceramics have been catching great interest especially in biomedical industries due to their excellent mechanical properties combined with biocompatibility and high chemical resistance. Aside from that, the combination of strength, toughness, chemical inertness and low thermal conductivity is advantageous for zirconia to be used in various engineering applications including automotive engine parts, fuel cells, and oxygen sensors. The superior mechanical properties are contributed by transformation toughening. However, one of the major drawbacks for zirconia is its susceptibility to low temperature degradation (LTD) which causes properties deterioration. LTD is highly dependent on the grain size of zirconia. From previous literatures, small grain can be obtained by conventional sintering at low temperature which would also produce less dense ceramics. Microwave assisted sintering has been developed in order to accelerate densification mechanism while decelerating grain growth. In this research, the comparison between microwave sintering and conventional sintering on the mechanical properties and microstructural evolution of 3 mol% yttria-stabilised zirconia were studied. Green bodies were compacted and sintered at various temperatures ranging from 1200 ºC to 1500 ºC. The result showed that microwave assisted sintering was beneficial in enhancing the densification and mechanical properties of zirconia, particularly when sintered at 1200 ºC. It was revealed that as the sintering temperature was increased to 1400 ºC and beyond, the grain size and mechanical properties for both microwave- and conventional-sintered ceramics were comparable thus suggesting that at the sintering temperature where densification mechanism was activated, grain size was strongly influenced by the sintering temperature rather than the sintering mode. In term of ageing behaviour, microwave assisted sintering was observed to delay the degradation process where the monoclinic content is less than 1% after 48 hours of exposure compared to conventionally sintered sample which recorded value more than 5%. However, after 100 hours of exposure to ageing environment, monoclinic content spike up to 31% for microwave- and 24% for conventional- sintered samples. The result suggested that small difference in grain size would give impact on the ageing behaviour of zirconia ceramics.